Agronomic Characteristics of Three Introduced Genotypes of Kailan Plants in Tropical Lowlands - Ade Sumiahadi; Wahyudin Wahyudin (Jurnal Ilmu Pertanian Indonesia, 2025)
Kailan has strong selling power, making it an attractive commodity for farmers. Plant introduction in a breeding program is one of the attempts being made to boost commercial kailan yield in Indonesia. The purpose of this introduction was to develop new varieties with high production, good yield quality, resistance to plant pest assaults, and adaptation in a variety of situations. The study sought to assess the agronomic properties of several imported kailan genotypes when grown in tropical lowlands. This experiment was conducted from May to July 2023 in the experimental field of the Faculty of Agriculture at Universitas Muhammadiyah Jakarta, South Tangerang City. The study employed a Randomized Complete Block Design with one treatment factor, the kailan genotype, with five levels, including three introduced genotypes (KI001, KI002, and KI003) and two national varieties as comparators (Nita and Nemo). The results revealed that the introduced genotype KI003 had superior total fresh weight and marketable fresh weight features than the other introduced genotypes and all comparator varieties. The introduced genotypes KI001 and KI002 share the same agronomic features as the two comparator varieties. The study found that all introduced varieties could adapt well to lowland tropical climatic conditions, however only the introduced genotype KI003 demonstrated superior adaptation when compared to the comparator types. Keywords: Brassica oleracea L, genetic variation, plant breeding, plant introduction